HDV epidemic in Central Italy is stable over the last two decades and is characterized by the circulation of multiple HDV sub-genotypes 1 inducing different inflammatory stimuli. (March 2023) - Salpini, R.; Piermatteo, L.; Torre, G.; D'Anna, S.; Khan, S.; Duca, L.; Bertoli, A.; Malagnino, V.; Paba, P.; Ciotti, M.; Lenci, I.; Francioso, S.; et al.
Abstract : Background: In Italy, HDV-prevalence and its fluctuations over time are controversial while an extensive characterization of HDV-infected patients is missing. Aim: To assess HDV-seroprevalence in a large cohort of HBsAg-positive subjects, followed in Central Italy over time, and the epidemiological/virological characteristics of HDV-infected patients. Methods: 1, 579 consecutive and well-characterized HBsAg-positive patients, firstly referred to Tor Vergata-University-Hospital from 2005-2022, were included. HDV-RNA was quantified by a commercial assay (LLOQ:100copies/ml) and HDV sub-genotypes were defined by phylogenetic-analysis. Results: Among 1, 579 HBsAg-positive patients, 45.3% (715/1579) received HDV-screening with an increasing temporal-trend: 17.1% (2005-2010), 43.2% (2011-2015), 56.5% (2016-2019), 75.8% (2020-2022). The lack of HDV-screening significantly correlated with normal ALT (OR[95%CI]:1.69[1.28-2.22], P<0.001) and being Italian (OR[95%CI]:1.4[1.12-184], P=0.005), while no factors were identified in 2020-2022. Overall, this suggests a higher awareness towards HDV-screening in all HBsAg+ in recent years. 13.4% (96/715) of HDV-screened patients resulted anti-HDV+ with a stable temporal trend: 10.7% (2005-2010), 15.6% (2011-2015), 10.8% (2016-2019), 10% (2020-2022). Among them, 80.5% had detectable HDV-RNA (median[IQR]log:4.6[3.6-5.6]copies/ml) with altered ALT in 89.3% (median[IQR]:92[62-177]U/L). Anti-HDV positivity was higher in patients from Eastern Europe than from Italy (23.6% versus 12.9%, P=0.002). Notably, anti-HDV+ patients from Eastern Europe were younger (44[37-54] versus 53[47-62]years, P<0.001) with higher HDV-RNA (4.8[3.6-5.8] versus 3.9[1.4-4.9]copies/ml, P=0.016) and HBsAg (9, 461[4, 159-24, 532] versus 4, 447[737-13, 336]IU/ml), P=0.032), indicating more pronounced HDV-replication. Phylogenetic-analysis revealed the circulation of HDV sub-genotype 1a (25.9%), 1b (33.4%), 1c (25.9) and 1d (14.8%). Notably, sub-genotype 1a and 1c correlated with 3xULN ALT compared to 1b and 1d (75%% versus 27.3%, P=0.039). Conclusions: The awareness to request HDV-screening is increasing over time even if some gaps remain to achieve HDV-screening in all HBsAg-positive patients. Immigration from Eastern Europe contributes to the circulation of HDV-strains with enhanced replication. The detection of different sub-genotypes, triggering variable inflammatory stimuli, supports the need to expand HDV molecular characterization.